Littre hernia in children: A clinical aspect - Bakal, Unal; Tartar, Tugay; Sarac, Mehmet; Kazez, Ahmet (Aves, 2019)
Background/Aims: Littre hernia (LH) is difficult to distinguish from other hernias until complications arise. In this research, we present the details of diagnosis, treatment, and frequency of LH cases with differentiated clinical properties. Materials and Methods: Littre hernia prevalence, clinical properties, and treatment details of cases diagnosed as incarceration/strangulation (I/S) of hernias between December 1996 and December 2017 were retrospectively investigated. Results: Incarceration/strangulation was detected in 403 out of 3758 hernias within 21 years. Four cases were detected as LH (0.09%) in 403 I/S patients. Partly reduced 2 cases were treated by resection/anastomosis with the abdominal approach. Conclusion: The possibility of LH in strangulated or partly reduced hernias should be considered. The abdominal approach may be necessary in nonreducible hernia with possible LH patients.
Keywords: Littre hernia; Meckel's diverticulum; strangulation; children